Technical efficiency of small and medium enterprise in Malaysia: a stochastic frontier production model - Radam, Alias; Abu, Mimi Liana; Abdullah, Amin Mahir (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
Small and medium enterprises (SMEs) play a vital role in the Malaysian economy and are considered as the backbone of industrial development in the country. However, SMEs’ value added is very much lower than that of large scale enterprises. The low productivity of physical inputs or factors efficiency may be attributed to the low level of value added. The objective of this study is to determine the technical efficiency of 7360 small and medium enterprises for the year 2004 using stochastic frontier model. Results show that the number of firms considered technically efficient is only 3.06 percent of the total firms, while total technical inefficiency varies from 0.30 to 97.10 percent. Thus, policy makers have to play an important role in promoting economies of scale and developing technical skills of labors, which will lead to higher efficiency levels among SMEs.